Bilateral middle cerebellar peduncle lesions: Neuroimaging features and differential diagnoses. Issue 10 (5th August 2020) - Jiang, Jiwei; Wang, Jirui; Lin, Meiqing; Wang, Xiaoting; Zhao, Jinli; Shang, Xiuli
Abstract: Objectives: Lesions limited to the bilateral middle cerebellar peduncles (MCPs) are uncommon. This retrospective study investigated diseases with a proclivity for the bilateral MCPs and explored the associations between their neuroimaging features and clinical findings for the differential diagnosis of such lesions. Methods: We enrolled 26 patients who were admitted to our department between January 2016 and March 2019 with bilateral MCP abnormalities on magnetic resonance imaging (MRI). The demographic, clinical, and neuroimaging characteristics, and the biomarkers and diagnoses were evaluated. Results: Although all patients exhibited symmetrical bilateral MCP hypointensities on T1‐weighted imaging and hyperintensities on T2‐weighted and fluid‐attenuated inversion recovery imaging, they were diagnosed with different conditions. Diagnoses included acute cerebral infarction (ACI) ( n = 9, 34.62%), Wallerian degeneration (WD) ( n = 8, 30.77%), multiple system atrophy (MSA) ( n = 6, 23.08%), neuromyelitis optica (NMO) ( n = 1, 3.85%), heroin‐induced leukoencephalopathy ( n = 1, 3.85%), and primary central nervous system lymphoma (PCNSL) ( n = 1, 3.85%). Patients with ACI exhibited bilateral MCP‐restricted diffusion hyperintensities on diffusion‐weighted imaging and corresponding stenosis or occlusion of the vertebrobasilar system. The initial MRI of patients with WD depicted pontine infarctions, while symmetrical MCP lesions were observed on follow‐up MRI. Symmetrical MCP lesions, cruciform hyperintensity, and marked atrophy in the posterior fossa were characteristic manifestations of MSA. Longitudinally extensive myelitis affecting more than three vertebral segments on cervical MRI and positive serum AQP4‐IgG may be indicative of NMO. Heroin‐induced leukoencephalopathy was characterized by extra‐symmetrical lesions in the posterior limbs of the internal capsules, while the anterior limbs were spared. PCNSL was indicated by a significant and characteristic "fist" sign on contrast‐enhanced MRI. Conclusions: Bilateral MCP lesions were most frequently observed in cerebrovascular diseases, followed by neurodegenerative diseases, inflammatory diseases, toxic encephalopathies, and lymphomas. Our findings demonstrate that bilateral MCP signal abnormalities are more common in patients with ACI and WD, with fewer degenerative processes than previously believed. The high frequency of WD may be attributed to the specific awareness of this pathology. WD can also present with stage‐related restricted diffusion and should not be mistaken for a new infarction. The symmetrical bilateral MCP hypointensities on T1‐weighted imaging and hyperintensities on T2‐weighted imaging often raise concern regarding a demyelinating process. Our findings emphasize that neurologists should consider the aforementioned conditions and correlate the specific neuroimaging characteristics and medical history before arriving at the final diagnosis. Abstract : We report a retrospective case series of 26 patients with bilateral middle cerebellar peduncle (MCP) lesions and compared the differences in clinical presentations and neuroimaging features of their associated diseases. Our findings showed that symmetrical bilateral MCP lesions occurred in various pathologic conditions, which were most frequent in cerebrovascular diseases, followed by neurodegenerative diseases, inflammatory diseases, toxic encephalopathies, and lymphoma, and the features differed in manners that could aid in distinguishing among the diseases.